Tuberculosis management - some aspects of the role of the nurse manager - May Hattingh (AOSIS, 1981)
Evidence suggests that the rapid spread of tuberculosis began in the early 1920s when the gold and diamond mines were established. In the late 1940s when the first two tuberculosis drugs became available it was the doctor who prescribed and administered treatment to the patients. Although public health nurses were present in the field at this stage, they were few and far between and could not contribute much towards tuberculosis management.